Reachiing for the Heavens - Edward Thompson (Oz, 2014)
The Burj Khalifa, located in Dubai, United Arab Emirates, was crowned by the Council of Tall Buildings and Urban Habitat (CTBUH) as the tallest structure built by man. So striking was the achievement that the CTBUH, in their yearly awards ceremony, created a special category titled "Global Icon" to do justice for the achievement.